Modern Blasphemy Laws in Pakistan and the Rimsha Masih Case: What Effect—if Any—the Case Will Have on Their Future Reform - Matt Hoffman (Washington University Global Studies Law Review, 2014)
This Note will examine the current blasphemy laws in Pakistan, with a particular focus on the case of Rimsha Masih, who was charged with blasphemy in 2012 and ultimately acquitted in 2013. Although Rimsha’s case is unprecedented, it is far from a turning point for blasphemy laws in Pakistan for two reasons. First, Rimsha’s case was an outlier, as evidenced by the unique circumstances of her case, as well as subsequent events that reinforce that proposition. Second, the nature of the political-religious-legal system in Pakistan makes the blasphemy laws and their enforcement a far more complicated issue than what occurs in a courtroom can explain. The very nature of Pakistan’s governmental, constitutional, and legal structure has created an extra-legal system of blasphemy law enforcement grounded in traditional notions of Islam and enforced in large part through vigilantism. If reform is to be achieved, it is in that arena where it must take place.
Keywords: Pakistan; blasphemy; Rimsha Masih; extra-legal; enforcement; Islam; aquittal; reform; religion; tradition; democracy; democratic; Western; church and state; church; vigilantism